Video-based testing in sporting officials: A systematic review. (July 2019) - Kittel, Aden; Larkin, Paul; Elsworthy, Nathan; Spittle, Michael
Abstract: Objectives: Decision-making is the most important skill for sporting officials, consequently, assessment of this skill is becoming increasingly popular in the literature. There is considerable interest in the use of video-based methods to assess decision-making of officials in controlled, off-field environments. Design: Systematic review of the literature examining video-based testing in sporting officials. Methods: Using the keywords "umpire", "referee", "sport officials", "decision making" and "judgement", a comprehensive search was conducted in February 2018 on electronic databases (SPORTDiscus, Medline, PsycInfo, Google Scholar). Inclusion criteria included full text articles from January 2000 to January 2018 published in peer-reviewed journals. Only 'central' or 'field' officials were included in this review (i.e., assistant referees, touch judges were excluded). Results: The search yielded 27 studies. The majority of articles were specific to soccer officials. Overall, video-based testing appears to be a valid measure of decision-making differentiating between performance levels. This review highlighted a high degree of variability among the methods applied, with varied participation groups, clip type used, and influences on decision-making. The reporting of reliability and implementation of transfer tests was rarely incorporated in the research. Conclusions: Video-based testing appears to be a valid measure of decision-making of officials in an off-field, controlled environment. This research area would be advanced through further investigation into sports other than soccer, examination of transfer to match performance testing, reporting the reliability of the test, reporting decisional accuracy rather than solely number of decisions, and investigation of additional video modes. Highlights: Video-based testing appears to be a valid measure of decision-making for officials. Transfer to on-field performance is a key consideration for off-field testing. Efficacy of new video modes must be assessed for off-field decision-making testing.